A Sociological Analysis Of The English Translation Of Santi Ii Heian Senlin - Deng, Gaosheng (2024)
This thesis is structured concerning three main objectives. Firstly, it aims to scrutinize the conducive field and external environment supporting the translation of Santi II, aided by both Chinese government and non-governmental forces. Secondly, the thesis seeks to delve into Martinsen’s habitus, exploring how he approaches character portrayal within Santi II. Lastly, it intends to analyze the substantial impact on the capital accumulation of the author and translator following the successful translation of Santi II.